Production of micro- and nanoscale silicon granules using powder technology - Mamirov Abduvoxid Muxammadamin o’g’li; Kodirov Sardorbek Anvar o’g’li (Zien Journals, 2022)
This paper describes in detail the operations performed on the extraction of nanostructures by the powder method, the use of powder technology and the purification of silicon granules obtained from the pulverization technology using a magnetic field (magnetic method), which is one of the most convenient methods of purification. X-ray diffraction analysis of granulated silicon semiconductor material to the nanoparticle state is shown. The final product consists of granules. Preliminary research shows that silicon powders range in size from 400 nanometers to 1,000 micrometers, and that their surface is made up of a variety of rough irregularities.
Keywords: Nanostructure; silicon; metallurgy; granule